BERHIMPUN DAN TERSEBAR: MENIMBANG DUA MODEL EKLESIOLOGI - Joas Adiprasetya (Diegesis : Jurnal Teologi, 2023)
This article intends to discuss and compare two ecclesiological models, namely, the gathered church and the scattered church, and to find their relevance to the life of the post-pandemic churches. By surveying several texts of Acts and the ecclesial practices in some eras in enlivening both models, the article attempts to discover some paradigmatic patterns of being the church. The result of this research is expected to be beneficial for constructing an ecclesiology for the post-pandemic season.